The place of the Amazon in Brazil development strategy - Kim, Ester Hee (2023)
The importance of the Amazon has been highlighted by internal and external stakeholders throughout decades. However, concerns regarding the Amazon Forest and the environmental governance have soared in Brazil in the last four years, due to many contradictory measures taken by a far-right government with no clear policy towards the Amazon region. This paper aims, from a multidisciplinary approach marked by the relationship between the Amazon and the International Relations studies, followed by the explanation of policies taken by the Brazilian government from 1980 to 2020, understanding the dichotomy surfaces towards the Amazon through the different political and economical phases. As part of this analysis, this study has collected a dataset of information, using different sources across varies stakeholders (i.e. governments, NGO, research institutions, multilateral banks) to provide a broader view about this complex but also fascinating treasure, which is the Amazon Forest. The finding of this study provides a clear message about the importance of the dialogue between stakeholders, given the multifaceted perceptions and perspectives, and protect the Forest should be the primary goal in any government, as scientific data must a tool for this objective.